Convenient Fires and Floods and Impossible Archival Imaginaries: Describing the Missing Records of Children's Institutions - Laurent, Nicola; O’Neill, Cate; Wright, Kirsten (Archivaria)

(untitled) (Association of Canadian Archivists, 2022)
This article concerns one notable feature of narratives around child welfare records: the prevalence of stories of records destroyed in natural disasters. These stories have the power to rouse strong emotions for people who grew up in institutional “care.” Care Leavers, many of whom have a justifiable lack of trust in institutions and authority as a result of their childhood experiences, are skeptical about the supposed loss of their records in fires and floods. They remain suspicious that the records do exist but are being withheld to protect the reputations of the institutions. This article considers Gilliland and Caswell’s notion of “archival imaginaries” in the context of missing, lost, or inaccessible child welfare records in Australia. The authors argue for an approach to describing these records that is not only person centred but also trauma-informed. The article presents two case studies that demonstrate the potential of applying this approach when describing records supposedly destroyed by fires and floods. Descriptions need to document the full story of the records, whether they materially exist or not, in a way that validates and acknowledges Care Leavers’ strong feelings about records and demonstrates archival organizations’ commitment to remediating the damage and hurt caused by past practices.